Maternal and Fetal Morbidity Associated With Uterine Rupture of the Unscarred Uterus. Issue 3 (September 2016) - Gibbins, K.J.; Weber, T.; Holmgren, C.M.; Porter, T.F.; Varner, M.W.; Manuck, T.A.
Abstract : ( Am J Obstet Gynecol. 2015;213:382.e1–e6) Uterine rupture is a serious condition that can jeopardize the health of both mothers and their unborn children. Rupture usually occurs in a uterus that has been scarred as a result of a previous cesarean delivery. There are relatively little data regarding the outcomes for mothers and neonates following rupture of an unscarred uterus, as this is such a rare complication. In the small number of reported cases of primary rupture, it was found to be associated with a perinatal mortality rate of 12% to 35% and a hysterectomy rate of 20% to 31%. The authors of this article designed their study to better understand the obstetric and neonatal characteristics surrounding primary rupture as well as its outcomes. The authors also evaluated uterine ruptures in scarred and unscarred uteruses and compared characteristics between these 2 groups.